Answer:
a) [tex]f'(x)=6[/tex]
b) [tex]f'(x)=12[/tex]
c) [tex]f'(x)=2kx[/tex]
Step-by-step explanation:
To find : From the definition of the derivative find the derivative for each of the following functions ?
Solution :
Definition of the derivative is
[tex]f'(x)= \lim_{h \to 0}(\frac{f(x+h)-f(x)}{h})[/tex]
Applying in the functions,
a) [tex]f(x)=6x[/tex]
[tex]f'(x)= \lim_{h \to 0}(\frac{6(x+h)-6x}{h})[/tex]
[tex]f'(x)= \lim_{h \to 0}(\frac{6x+6h-6x}{h})[/tex]
[tex]f'(x)= \lim_{h \to 0}(\frac{6h}{h})[/tex]
[tex]f'(x)=6[/tex]
b) [tex]f(x)=12x-2[/tex]
[tex]f'(x)= \lim_{h \to 0}(\frac{12(x+h)-2-(12x-2)}{h})[/tex]
[tex]f'(x)= \lim_{h \to 0}(\frac{12x+12h-2-12x+2}{h})[/tex]
[tex]f'(x)= \lim_{h \to 0}(\frac{12h}{h})[/tex]
[tex]f'(x)=12[/tex]
c) [tex]f(x)=kx^2[/tex] for k a constant
[tex]f'(x)= \lim_{h \to 0}(\frac{k(x+h)^2-kx^2}{h})[/tex]
[tex]f'(x)= \lim_{h \to 0}(\frac{k(x^2+h^2+2xh-kx^2)}{h})[/tex]
[tex]f'(x)= \lim_{h \to 0}(\frac{kx^2+kh^2+2kxh-kx^2}{h})[/tex]
[tex]f'(x)= \lim_{h \to 0}(\frac{h(kh+2kx)}{h})[/tex]
[tex]f'(x)= \lim_{h \to 0}(kh+2kx)[/tex]
[tex]f'(x)=2kx[/tex]